1994
DOI: 10.1007/bf01627684
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic study of the lumbar region applied to multiplanar imaging techniques: Importance and use of oblique vertical sections

Abstract: This anatomic study of the lumbar region (as defined by Rouvière [11]) applied to multiplanar imaging techniques was carried out both in the cadaver and in vivo. The cadaver study (5 cases) consisted of anatomic sections (transverse, sagittal, frontal and oblique) and computerised three-dimensional reconstructions after CT studies on subjects injected with colored and radio-opaque latex. The in vivo study (4 cases) used MRI sections and three-dimensional ultrasound sections coupled with the pulsed doppler. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…24 The Petit triangle is also conducive in urology, neurosurgery and surgery as an approach to the retroperitoneal space. [25][26][27][28] In this study, the inferior lumbar triangle was bilaterally present in all human fetuses considered. In an autopsy study conducted in adults, Loukas et al observed Petit's triangle in 82.5% of cases, and Starczewski in 89% of cases, somewhat more often on the left side.…”
Section: Discussionmentioning
confidence: 99%
“…24 The Petit triangle is also conducive in urology, neurosurgery and surgery as an approach to the retroperitoneal space. [25][26][27][28] In this study, the inferior lumbar triangle was bilaterally present in all human fetuses considered. In an autopsy study conducted in adults, Loukas et al observed Petit's triangle in 82.5% of cases, and Starczewski in 89% of cases, somewhat more often on the left side.…”
Section: Discussionmentioning
confidence: 99%